Thermophilic biohydrogen production utilizing green-synthesized hydroxyapatite (HAP): insights into substrate optimization and biogranule formation - Zisha, Shishita Zahan; Che Man, Hasfalina; Omar, Rozita; Abdul Rashid, Suraya; Ping, Tan Jian; Abdul Manaf, Shareena Fairuz; Mumtaz, Tabassum; Jamali, Nur Syakina (Springer, 2025)
This study presents an integrated approach for enhancing thermophilic biohydrogen production from palm oil mill effluent (POME) using eco-friendly hydroxyapatite (HAP) synthesized from waste eggshells. The synthesized HAP was applied as a bio-additive to stimulate microbial activity and facilitate cell immobilization. Batch fermentation was performed under thermophilic conditions (60 °C) using a mixed culture dominated by Thermoanaerobacterium thermosaccharolyticum, with varying POME concentrations (4–20 g/L) to determine the optimal substrate level. The maximum hydrogen yield (2.19 ± 0.43 mol H2/mol sugar) and hydrogen production rate (1.24 ± 0.62 L H2/L·day) were achieved at 16 g/L POME, corresponding to enhanced VFA production via the butyrate–acetate pathway. Beyond this concentration, hydrogen production declined due to probable substrate inhibition and VFA accumulation. Additionally, the effects of organic loading rate (OLR) were evaluated over 183 days to investigate the relationship between reactor performance and microbial structure. The optimal hydrogen production occurred at OLR 4 (8.89 g VS/L), where SEM analysis revealed compact, EPS-rich bio granules that supported stable hydrogenogenic activity and efficient biomass retention. These findings demonstrate the synergistic effect of green HAP supplementation and optimal substrate conditions in promoting microbial granulation and metabolic efficiency, offering a sustainable strategy for biohydrogen production from high-strength wastewater.